PELAKSANAAN PELAYANAN PUBLIK PADA SISTEM ANGKUTAN UMUM MASSAL (SAUM) TRANS METRO PEKANBARU - Sanny Aswimbi; Chalid Sahuri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Trans Metro is one of transportation product which has created by Trans Metro Pekanbaru due to provide transportation at Pekanbaru city. Custumer able to use this transportation service for making their activities easily. At this time, Trans Metro Pekanbaru in giving the services has not properly with customers need. These sign in complain from customer.This study is analysis the transportation services in Trans Metro Pekanbaru due to know the problems from those services.The method that will be used in this study is researcher do the analysis descriptive qualitative with the purpose is getting the comphrehensive result and detail based on interview result with people and direct observation wit analysis transportation services at Trans Metro Pekanbaru.Based on study due to public services at system transportation general of Trans Metro Pekanbaru is using 5 dimension are tangible, reability, responsiviness, assurance, and empathy. The transportation services at trans Metro Pekanbaru already gived the maximum quality, even it still has a few non optimal fot the quality . From the study result known that the problems in transportation services of Trans Metro Pekanbaru are limitation of human resources, low acomodation aand minim the budget.Keyword : Services, Public, Mass Transit Systems